ANALISIS KINERJA KEUANGAN PERUSAHAAN YANG TERMASUK DALAM KELOMPOK INDEKS LQ 45 DENGAN MENGGUNAKAN EVA PADA BURSA EFEK JAKARTA (Studi Kasus Pada Bursa Efek Jakarta) - Noviar, Yan (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2011)
Abstract This Research is entitled “The Analysis of the Financial Performance Companies which Included in group make an index to LQ 45 by using EVA at Jakarta Stock Exchange in the Year of 2006”. As for target of this research to know the difference between the mean Economic Value Added ( EVA) of the public companies is merged into go to group of LQ 45 which have large asset and LQ 45 which have small asset. The research method used is case study of the public companies which is merged into go to group of LQ 45which are listed in Jakarta Stock Exchange. The definition of the large asset and the small asset is the amount of mean the sample of companies at index group LQ 45. While companies taken as sample is companies which enlist in two period of the announcement of BEJ or one full year of (2006) and data used in this research is data of secondary in Web JSX. From the result of hypothesis test, known the four of concluded, first not there are difference which is significant between mean EVA of the companies is merged into go to group of LQ 45 which have large asset and mean of EVA of the companies is merged into go to group of LQ 45 which have small asset. Result of test of t, known the value of t obtained for different test EVA equal to 0.86 smaller than t of tables of equal to 1.960.